2021
DOI: 10.34123/semnasoffstat.v2020i1.497
|View full text |Cite
|
Sign up to set email alerts
|

How Can Machine Learning Help the Authorities?

Abstract: Corona Virus Desease (COVID-19) pandemic is causing health crisis in every region in the world, especially in Indonesia. One of the effective methods against the virus is wearing face mask in public place as the regulation made by the authorities. This paper introduces face mask detection that can be used by the authorities to make mitigation, evaluation, prevention, and action planning against COVID-19. On the other hand, this solution can be used as communication tool to evaluate people’s habit on wearing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several kinds of research have been carried out related to the provision of user needs automatically and the selection of the distribution of masks. In their study, Sanjaya et al [3] successfully detected people's faces using the MobileNetv2 image classification method for 25 cities in Indonesia and concluded that the five cities were the highest and the five lowest cities in the application of the use of masks in these cities. The detection process is integrated with surveillance cameras to check people who are not wearing masks.…”
Section: Related Workmentioning
confidence: 99%
“…Several kinds of research have been carried out related to the provision of user needs automatically and the selection of the distribution of masks. In their study, Sanjaya et al [3] successfully detected people's faces using the MobileNetv2 image classification method for 25 cities in Indonesia and concluded that the five cities were the highest and the five lowest cities in the application of the use of masks in these cities. The detection process is integrated with surveillance cameras to check people who are not wearing masks.…”
Section: Related Workmentioning
confidence: 99%